2018
DOI: 10.1021/acs.nanolett.8b04279
|View full text |Cite
|
Sign up to set email alerts
|

Self-Folded Three-Dimensional Graphene with a Tunable Shape and Conductivity

Abstract: Three-dimensional (3D) graphene architectures are of great interest as applications in flexible electronics and biointerfaces. In this study, we demonstrate the facile formation of predetermined 3D polymeric microstructures simply by transferring monolayer graphene. The graphene adheres to the surface of polymeric films via noncovalent π−π stacking bonding and induces a sloped internal strain, leading to the self-rolling of 3D microscale architectures. Micropatterns and varied thicknesses of the 2D films prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Regarding the multi-functional and multi-environmental responsive shape-changing soft robots, stimuli-responsive materials have been combined with carbon-based materials, such as graphene, graphene oxide sheets (GOs), or their hybrids due to their high electrical, thermal, and optical properties [48][49][50][51][52][53][54]. To fold, bend, or roll two-dimensional atomic scale paper, various elegant scientific and engineering strategies have been developed.…”
Section: Graphene/graphene Oxides (Go)-stimuli-responsive Composite Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the multi-functional and multi-environmental responsive shape-changing soft robots, stimuli-responsive materials have been combined with carbon-based materials, such as graphene, graphene oxide sheets (GOs), or their hybrids due to their high electrical, thermal, and optical properties [48][49][50][51][52][53][54]. To fold, bend, or roll two-dimensional atomic scale paper, various elegant scientific and engineering strategies have been developed.…”
Section: Graphene/graphene Oxides (Go)-stimuli-responsive Composite Gelsmentioning
confidence: 99%
“…To fold, bend, or roll two-dimensional atomic scale paper, various elegant scientific and engineering strategies have been developed. For example, Teshima et al introduced a swift and easy way to spontaneously bend or roll thin poly (chloro-p-xylylene) (parylene-C) film by transferring monolayer graphene onto the parylene thin layer ( Figure 3A) [48]. They demonstrated that the self-folding actuation of this bilayer was induced by reconfiguration of the molecules within the crystalline graphene, and other elements, such as 2D geometry design and thickness.…”
Section: Graphene/graphene Oxides (Go)-stimuli-responsive Composite Gelsmentioning
confidence: 99%
“…The beginning part of the fabrication process of the GMA was similar to that we previously reported to form a self-folding microroll. (8,9) First, sodium alginate was coated on SiO 2 substrates and the coated substrates were then immersed in calcium chloride to hydrogelate alginate with calcium ions. Next, the aqueous silk fibroin was coated and hydrogelated by immersing in methanol, and then the chemical deposition of the parylene layer was performed.…”
Section: Fabrication Of Gmamentioning
confidence: 99%
“…We have also reported that multilayered polymeric films with heterogeneous mechanical properties can form self-folded microrolls. (8,9) Through integration with a noncytotoxic batch release of a hydrogel-based sacrificial layer, the films autonomously fold into cylindrical shapes on the basis of differential strain gradients that depend on the film thickness. Various 3D cellladen microstructures form from 2D geometrical micropatterns, enabling the embedded cells to migrate and connect with each other.…”
Section: Introductionmentioning
confidence: 99%
“…2D materials often have different properties from their bulk counterparts such as increased strength 7 and electrical conductivity. 8 2D semiconductors may exhibit a change in electronic states from confinement in 1D. 9 Thin films are often required for the creation of devices from nanomaterials for practical applications and can often be made into flexible devices such as thin film solar cells 10 or photodetectors.…”
mentioning
confidence: 99%